2009
DOI: 10.3747/co.v16i1.393
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors as Therapy for Advanced, Metastatic, and Recurrent Non-Small-Cell Lung Cancer: A Canadian National Consensus Statement

Abstract: PurposeTo provide consensus recommendations on the use of epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) in patients with advanced or metastatic non-small-cell lung cancer (NSCLC). MethodsUsing a systematic literature search, phase II trials, randomized phase III trials, and meta-analyses were identified for inclusion. ResultsA total of forty-six trials were included. Clear evidence is available that EGFR-TKIs should not be administered concurrently with platinum-based chemotherapy as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 74 publications
0
16
0
2
Order By: Relevance
“…Among ADC patients, better response rate was also reported in tumors with prominent lepidic (formerly bronchioloalveolar carcinoma or BAC) growth pattern [5,6]. However, molecular studies have demonstrated that the presence of mutations in the tyrosine kinase domain (TKD) of the EGFR gene is a better predictor of response than ADC histology [4,7,8]. In contrast, epithelial-mesenchymal transition (EMT) is a potential marker of resistance to EGFR TKI therapy [9,10].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Among ADC patients, better response rate was also reported in tumors with prominent lepidic (formerly bronchioloalveolar carcinoma or BAC) growth pattern [5,6]. However, molecular studies have demonstrated that the presence of mutations in the tyrosine kinase domain (TKD) of the EGFR gene is a better predictor of response than ADC histology [4,7,8]. In contrast, epithelial-mesenchymal transition (EMT) is a potential marker of resistance to EGFR TKI therapy [9,10].…”
Section: Introductionmentioning
confidence: 89%
“…Higher response rates to EGFR TKI therapy have been observed in NSCLC patients who are East Asian, never-smokers, female or present with adenocarcinoma (ADC) histology [1,3,4]. Among ADC patients, better response rate was also reported in tumors with prominent lepidic (formerly bronchioloalveolar carcinoma or BAC) growth pattern [5,6].…”
Section: Introductionmentioning
confidence: 95%
“…Together, these two mutations account for almost 90% of all EGFR mutations in NSCLC [20]. Response rates to EGFR-TKIs range from 48% to 90% for patients with EGFR mutations, while responses are less common in patients without a mutation (5-31%) [21]. Interestingly, two mutant-specific antibodies directed against the most common mutant forms of the EGFR oncoprotein have been recently developed for IHC use: 15-bp deletion (E746_A750del) in exon 19 and the L858R point mutation in exon 21 [22].…”
mentioning
confidence: 98%
“…4.1.5.3.12. 8-(3, 4-Dimethoxyphenylamino)-1-(2-methoxyethyl) oxazolo [4,5-g] 3.29 (3H, s); 13 C NMR (125 MHz, d: 157.34, 153.50, 148.46, 147.02, 146.04, 145.58, 132.27, 130.71, 115.19, 111.84, 111.66, 108.71, 106.49, 100.57, 67.66, 58.08, 55.74, 55.60, 41.90. 4.1.5.3.13.…”
Section: Purity Analysismentioning
confidence: 99%